Ultrasonic optic nerve sheath diameter could improve the prognosis of acute ischemic stroke in the intensive care unit - Li, Cong; Wang, Cui-Cui; Meng, Yan; Fan, Jia-Yu; Zhang, Jie; Wang, Li-Juan (Frontiers in Pharmacology, 2022)
Objectives: Stroke patients with high intracranial pressure (ICP) may have poor prognosis. Non-invasive ultrasonic optic nerve sheath diameter (ONSD) could evaluate increased ICP. To investigate whether ONSD is valuable for prognosis of patients with acute ischemic stroke (AIS). Methods: AIS receiving intensive care were recruited with the Glasgow Coma Scale (GCS) score. Patients in group A underwent ultrasonic ONSD to assess ICP voluntarily, whereas group B without ONSD. Patients were followed up at discharge and once a week for 3 months with Glasgow Outcome Scale (GOS) score (four to five scores indicated good prognosis and one to three scores indicated poor prognosis). Results: Forty-nine patients were included. GCS scores did not differ significantly between groups A (26 patients) and B (8 ± 3 vs. 7 ± 3, p < 0.05). In group A, ONSD was 5.01 ± 0.48 mm, which correlated with GCS score (p < 0.05). At discharge, the GOS score was higher in group A than in group B (3.35 ± 1.35 vs. 2.57 ± 1.121, p = 0.034). The proportion of patients with a good prognosis was higher in group A than in group B (46.2% vs. 13.0%, p = 0.006). At discharge and after 3 months of follow-up, ONSD at admission was correlated with the GOS score in group A (r = -0.648 [p < 0.05] and -0.731 [p < 0.05], respectively). After 3 months of follow-up, the GOS score was higher in group A than group B (3.00 ± 1.673 vs. 2.04 ± 1.430, p < 0.05). The proportion of patients with a good prognosis was higher in group A than in group B (46.2% vs. 21.2%, p = 0.039). The Kaplan-Meier curve showed a higher rate of good prognosis in group A than in group B. ONSD (p < 0.05) was an independent predictor of poor prognosis. Conclusion: Non-invasive ultrasonic ONSD could be useful in improving the prognosis of patients with AIS receiving intensive care.